ANALYSIS OF THE INFLUENCE OF DRILL PIPE COLUMN DEFORMATION ON THE ACCURACY OF PASSAGE MEASUREMENT - Зварич, Галина; Матеїк, Галина (SWorldJournal, 2025)
The work considers the elements of the deformation of the drill string on the error of measuring the bit penetration in the process of drilling oil and gas wells. By processing information on the feed of the drilling tool, indicators of the efficiency of